Behaviour problems in dogs : the relationship between reported behaviour problems, causal attributions, and ineffective discipline - Wong, Poh Wan *; Cheong, Sau Kuan * (Sunway University College, 2010)
The purpose of this study was to examine the relationship between causal attributions of dogs' behaviour problems, ineffective discipline, and reported behaviour problems. One hundred dog owners (50 males and 50 females) from Selangor and Kuala Lumpur were surveyed using questionnaires containing the Causal Dimension Scale, Dog Discpline Scale, and Canine Behaviour Checklist. Participants were above 18 years old and owned a dog at the time of participation in this study. Results indicated that higher perceptions of stability of behaviour problems were significantly related to higher reported behaviour problems and higher ratings of ineffective discipline. Higher ineffective discipline was also related to higher reported behaviour problems. Lastly, ineffective discipline was found to be a mediator between perception of stability and reported behaviour problems. In conclusion, dog owners' perceptions affect their disciplining behaviours which ultimately influence the behaviour of their dogs.